Oprah : a biography - Kelley, Kitty (New York : Crown Publishers, 2010)
An extensively researched biography of Oprah Winfrey examines the personal life and career of the influential icon and discusses her place in modern American culture.
Keywords: Winfrey, Oprah; Television personalities -- United States -- Biography; Actors -- United States -- Biography